2016
DOI: 10.2298/tsci16s5259m
|View full text |Cite
|
Sign up to set email alerts
|

Comparative exergetic performance analysis for certain thermal power plants in Serbia

Abstract: Traditional methods of analysis and calculation of complex thermal systems are based on the first law of thermodynamics. These methods use energy balance for a system. In general, energy balances do not provide any information about internal losses. In contrast, the second law of thermodynamics introduces the concept of exergy, which is useful in the analysis of thermal systems. Exergy is a measure for assessing the quality of energy, and allows one to determine the location, cause, and real size of losses inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…One such study showing the importance of exergy analysis for energy systems was carried out by Yıldızhan [4], who found that the exergy consumption of harvested crops was more remarkable than their calculated energy consumption. This finding is parallel to the research done by Mitrovic et al [5], who studied the performance of four thermal power plants from energetic and exergetic viewpoints. They found that exergy analysis results offered improved plant performance.…”
Section: Introductionsupporting
confidence: 76%
“…One such study showing the importance of exergy analysis for energy systems was carried out by Yıldızhan [4], who found that the exergy consumption of harvested crops was more remarkable than their calculated energy consumption. This finding is parallel to the research done by Mitrovic et al [5], who studied the performance of four thermal power plants from energetic and exergetic viewpoints. They found that exergy analysis results offered improved plant performance.…”
Section: Introductionsupporting
confidence: 76%
“…The 15% castor oil biodiesel in diesel resulted in optimum engine performance with improved thermal and exergetic efficiency [9]. The internal losses in any thermodynamic systems could not be evaluated by first law of thermodynamics [10,11]. The energy loss in thermal power equipments could not be evaluated based on only the first law of thermodynamics [12].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the work [16] is to present how nature-inspired swarm intelligence (especially particle swarm optimization) can be applied in the field of power plant optimization and how to find solutions for the problems arising and also to apply exergoeconomic optimization technics on TPP. A comparative analysis of four TPP performances from the energetic and exergetic viewpoint has been conducted in [17]. Thermodynamic models of the plants are developed with primary objectives to analyze the system components separately and to identify and quantify the sites having largest energy and exergy losses.…”
Section: Introductionmentioning
confidence: 99%